Penerapan Model Kooperatif Tipe TGT untuk Meningkatkan Keaktifan Belajar Muatan Pendidikan Pancasila Kelas V - Iyan Iyan; Gina Anisahira; Ritha Tuken (ANWARUL, 2026)
Although cooperative learning models have been widely studied, research specifically addressing the improvement of learning engagement through the integration of Kahoot in the topic “Norms in My Life” at the elementary school level remains limited. This study aims to analyze and describe the improvement of fifth-grade students’ learning engagement through the implementation of the Teams Games Tournament (TGT) cooperative learning model assisted by Kahoot. This study used a qualitative approach with a Classroom Action Research (CAR) design conducted in two cycles, involving 34 students selected through purposive sampling. Data were collected through observation sheets, learning engagement questionnaires, and documentation, and were then analyzed using the qualitative descriptive analysis technique of the interactive model of Huberman and Saldana. The results showed that the implementation of the Kahoot-assisted TGT model was able to change students’ learning behavior from passive to more proactive, with learning engagement increasing from the low category at the beginning of the cycle to 83.54%, or the high category, at the end of Cycle II. This improvement was supported by the teacher’s instructional effectiveness, which reached 94.44%. These findings contribute to the development of digital cooperative learning and broaden understanding of the use of gamification in Pancasila Education content. The conclusion of this study emphasizes the importance of synergy between competitive games and digital technology in creating a dynamic learning ecosystem, and recommends optimizing digital instructional time management in its implementation. The implications of this study include strengthening the literature on digital cooperative learning and the practice of implementing the activity-based Independent Curriculum, while also opening opportunities for further studies on the long-term impact of gamification on students’ retention of normative values.